PEMANTAUAN PERTUMBUHAN PADI MENGGUNAKAN CITRA SATELIT LANDSAT 8 - I Made Satya Graha; Made Arya Bhaskara Putra (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2022)
This study aims to determine the relationship between rice growth parameters and vegetation index data from Landsat 8 satellite imagery. This study was conducted for six months and is located in Klungkung Regency. Each vegetation index was then associated with rice growth data. The results showed that the growth pattern of rice followed a parabolic curve whose shape was influenced by the growth parameters. There is a close relationship between the rice growth parameters and the vegetation index value. The vegetation index, which closely relates to all rice growth parameters, is RGVI, IPVI, and TVI, with an average R2 value of 0, respectively. .9328, 0.9066, and 0.8862, and the average SE values were 0.0637, 0.0872, and 2.2071, respectively. Each vegetation index has its advantages in predicting and determining the parameters of rice growth, including; (a) NDVI and DVI are suitable for estimating the age of rice, (b) RVI and TVI are suitable for estimating land cover by rice, (c) IPVI is suitable for estimating leaf chlorophyll values, (d) SAVI and MSAVI are suitable for use to estimate the height of rice, and (e) RGVI is suitable for estimating the number of clumps of rice.